Analysis, specification and verification requirements for control systems cloud training platforms - Elvira Faridovna Matveeva; Rainer Unland; Martin Gröger; Dietrich Brandt; Torsten Brinda; Vardan Surenovich Mkrttchian (Academy of Cognitive and Natural Sciences, 2014)
Digital control systems are now an essential and critical part of Cloud Training Platforms. Numerous methods, tools and standards have been developed to ensure that such systems will comply with their requirements. However, the development of such requirements often does not receive the same level of attention. Indeed, in the case of highly reliable, mission-critical or safety-related control systems, operating experience shows that problems due to inadequate requirements tend to outnumber those due to incorrect design and implementation. This paper proposes an approach to the analysis, specification and verification of Sliding Mode control systems requirements for Bus Cloud Triple H-Avatar.